Teachers Perspective on Redesigning Social Studies Curriculum for Student-Centered and Constructivist Learning: Empirical Study of Secondary Schools, Northern Region - Iddrisu Bariham; Evelyn Kuusozume Yirbekyaa; Anthony Bordoh (Social Education Research, 2022)
Effective, equitable, and student-centered Social Studies instruction occurs in an environment that is prepared and well designed for that purpose. The 21st Century Social Studies curriculum should be planned to allow teachers to adopt constructivist, student-centered pedagogies to improve students’ learning outcomes. However, it appears that most teachers in Ghana still apply traditional rote methods of instruction, which deprive students of the ability to acquire 21st-century learning due to weaknesses in the existing curriculum. This study was, therefore, conducted to explore from teachers how the Social Studies curriculum can be reformed to create room for active and student-centered learning. A cross-sectional research design was adopted for this study. Senior High School (SHS) Social Studies teachers in the Northern Region were the target population for the study (N = 175 teachers). Using Yamane’s (1967) formula for sample size determination, 151 teachers were randomly sampled for the study with a confidence level of 97% and a margin of error of ± 3%. Closed-ended item questionnaires were used to collect data from the respondents. The reliability of the items in the questionnaires was tested using the Cronbach alpha formula, which yielded α = 0.78, acceptable for the study. Using Statistical Package for the Social Sciences (SPSS), data were analyzed employing descriptive statistics such as frequencies, percentages, means, and standard deviations, and the results were presented in tables. The study discovered strong endorsement by teachers of the need for a new Social Studies curriculum that provides opportunities for meaningful learning; a call for Social Studies curriculum reform to create room for student-centered learning to improve students’ learning outcomes in line with SDG 4. The study recommends curriculum reforms, capacity-building programmes for teachers based on training needs, supply of relevant instructional resources, expansion of SHSs infrastructure, and rethinking the ban on SHS students’ use of phones and personal laptops on campuses.